Regulatory framework of GMOs and hybrid seeds in Nepal - Thapa, M (Agronomy Journal of Nepal, 2013)
Most of the farmers are aware of about hybrid seeds; however almost all farmers and even technicians are not quite known about GMOs and associated effects. It is unspoken that use of hybrids has no adverse effect on the environment, human/animal health and our ecosystem if managed properly. Since, Nepal is in a very infant stage in hybrid research and development; however the demand is increasing over time. National legislative mechanism, human resources and physical facilities are not well established in testing and regulation of GMOs. So it is necessary to encourage policy-makers to strengthen their commitment and provide strong policy and financial support to promote hybrid research and development in Nepal through public private partnership for import substitution. Strong regulatory mechanism should be developed and adopted to reduce the inflow of hybrids and regulation of GMOs from abroad. National legislative, administrative and technical competency on research and testing of seed, plants, food, feed and animals with GMOs should be strengthened and regularized along with public participation for making decision whether to allow or restrict the import of the GMOs. Public participation is necessary in the decision making process of production, import, handling and use of GMOs and hybrids. As GMOs are very new and unknown about its implication on human health and the biological diversity, people at all levels should be aware of both the positive and negative aspects of GMOs. As a part of the public awareness program, it is required to disseminate available information on GMOs and products thereof through appropriate media, languages and publications and concerned stakeholders including growers, consumers, and business entrepreneurs. Agronomy Journal of Nepal (Agron JN) Vol. 3. 2013, Page 128-137 DOI: http://dx.doi.org/10.3126/ajn.v3i0.9015